Role of Food Processing Training and Exposure Visits in Empowering the Rural Women Community - Malleswari, K.; Patil, Dattatraya; Sridhar, G.; Nagendra Prasad, B. (Prabandhan: Indian Journal of Management, 2015)
An impact study on food processing training and exposure visits conducted by the Krishi Vigyan Kendra (KVK) during the year 2011-2013 was evaluated. The total number of trainees who attended the programme during 2011-2013 was 200 (including on campus and off campus). The food processing trainees were trained out in the areas such as sorting, grading of agricultural commodities, post harvest technology aspects, making different kinds of pickles and curries, and preparing value added products from different field crops. Four groups, each containing 50 rural women having a minimum educational qualification of 10th (SSC) pass, were selected from the entire district including high altitude and tribal areas. The study revealed that the trainees were able to upgrade their knowledge in different areas of food processing . The study shows that the knowledge of the trainees in the different areas of food processing increased from 36.5% to 87.7%.